DAMPAK KEGIATAN PARIWISATA TERHADAP SOCIO ECONOMIC BEHAVIOR MASYARAKAT KOTA BANDA ACEH PASCA TSUNAMI - Teuku Muhammad Afiah; Abd. Jamal (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
AbstractAfter  the 2004 Earthquake and Tsunami Disaster in Aceh, the Aceh Province in in this case Banda Aceh city continues to strive to develop the developmentof the city both in terms of infrastructureand not least from the Tourism sector. The problem that occurs is whether the impact of tourism activitiesaffectsthe socio economic behavior in Banda Aceh city. The method use is descriptive method which conducts field surveys to see the result of the research.The results of the research obtained through the results of distributing questionnaires in qualitative form are compiled beforehand so that they become quantitative data. The quantitative values compiled are used on a Likert scale (Donal R. Couper, C. William Emory: 1997). One choice is scored with interval distance 1. The choice score is between 1,2,3,4 and 5.The results of the discussion of thei study indicate that impact of tourism activities has a positive and significant impact on the socio-economic community in the City of Banda Aceh Post Tsunami especially around tourist sites.Keywords: Tourism, Socio Economic Behavior, Business Opportunities, income.